A Robustness Reproduction of Tappin, Berinsky and Rand (2023): "Partisans' Receptivity to Persuasive Messaging is Undiminished by Countervailing Party Leader Cues" - Thomas Brailey; Edmund Kelly (Institute for Replication (I4R), 2024)
Tappin, Berinsky, and Rand (2023) find that the effectiveness of persuasive messaging is not diminished by countervailing in-party leader cues, using a survey experiment fielded in the United States. In this robustness reproduction, we briefly summarize the original design and results before blindly reproducing the main results and conducting several additional robustness checks. We find that the original results are reproducible and robust to several additional checks. In so doing we contribute to the collaborative effort between the Institute for Replication (I4R) and Nature Human Behaviour to replicate recent findings published in the latter, and more broadly to advancing replication in political science.
Keywords: 330